Перспективи розвитку природно-мовних технологій - Kislenko, Yu. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A class of information technologies, oriented at natural language processing is investigated. Such systems, generally, model the human speech activity, and their information core consists of a lingual processor and knowledge data, working for each other. Perspectives for this class of information technologies are analyzed from the viewpoint of the formal model of language offered by the author.